Paradox of inferiority: Indonesia’s Muslims attitude towards the Chinese minority until the Reformasi 1998 - Sahul Hamid Mohamed Maiddin,; Muhamad Rozaimi Ramle, (Penerbit UKM, 2024)
Indonesia has the largest Muslim population in the world with a total of around 217 million people. Despite being the world’s largest Muslim country, the economy is not controlled by the Muslims, but by the Chinese ethnic group who became Indonesian citizens since its independence in 1945. This article discusses the background of the 1998 reform movement, from Suharto’s grip to the Chinese ethnic group’s monopoly on Indonesia’s economy. It then analyzes the reasons for the unrest among Indonesian Muslims regarding the Chinese ethnic group’s domination, leading to the manipulation of religious sentiments to justify condemnation and attacks. The article also assesses its impact on the Chinese ethnic group in Indonesia and the development that has occurred after the reform movement. The methodology of this article is qualitative by utilizing both primary and secondary sources. The primary sources used in this article are newspaper reports, magazines, and government documents obtained both online and from the National Library of Indonesia, the National Archives of the Republic of Indonesia, and the National Archives of Malaysia. Journals and books were also used as secondary references. In general, this article finds that Indonesian Muslims are prejudiced against ethnic Chinese citizens due to the unequal economic distribution during the Suharto era and emotional manipulation led by a few groups in the name of Islam. Indonesian Muslims react because they feel inferior to the dominance of ethnic Chinese over the Indonesian economy, thus creating the paradox of Muslims as a minority.